2012
DOI: 10.15353/joci.v8i2.3047
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthy Records and Open Data

Abstract: The Open Data movement has assumed that that accurate data is available to demonstrate government expenditure and actions. However, in many countries, the records of government policies, activities and transactions that should provide the basis for a large proportion of government data are incomplete, inaccurate or inaccessible.  This will result in inaccurate data. This paper suggests that alongside the enthusiasm for Open Data, there needs to be parallel attention to ensuring that government records are mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In the UK, significant progress toward open government has been observed, with the establishment of the Data.gov.uk portal being the most significant development to allow open access to government data sets (Davies, 2010). The UK Government is increasing transparency, for instance, by opening up data on public spending and crime and has shown commitment to spreading the practice of openness globally (Thurston, 2012). Since 2012, “the United Kingdom has played a leading role in international efforts to share this open approach so that people across the world can hold their governments accountable” (Thurston, 2012, p. 18).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, significant progress toward open government has been observed, with the establishment of the Data.gov.uk portal being the most significant development to allow open access to government data sets (Davies, 2010). The UK Government is increasing transparency, for instance, by opening up data on public spending and crime and has shown commitment to spreading the practice of openness globally (Thurston, 2012). Since 2012, “the United Kingdom has played a leading role in international efforts to share this open approach so that people across the world can hold their governments accountable” (Thurston, 2012, p. 18).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The UK Government is increasing transparency, for instance, by opening up data on public spending and crime and has shown commitment to spreading the practice of openness globally (Thurston, 2012). Since 2012, “the United Kingdom has played a leading role in international efforts to share this open approach so that people across the world can hold their governments accountable” (Thurston, 2012, p. 18).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These case studies enable comparative work, analyzing the open government data policy setting and how it interacts with information management roles. The research explored the role of the information and records manager in practice in an open government environment, given that it is a critical actor in the delivery of open government data to citizens (Thurston, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Complete and accurate metadata may also send a more general signal to users about the quality of the dataset (Hernandez-Perez, Rodriguez-Mateos, Martin-Galan, & Garcia-Moreno, 2009;Schuurman, Deshpande, & Allen, 2008;Xiong, Hu, Li, Tang, & Fan, 2011;Zuiderwijk et al, 2012): and the extent datasets appear as high quality is likely to be an important driver of their use (Vetrò et al, 2016). Indeed, research has shown that many initial open data releases lacked descriptions and important contextual information that would allow people to evaluate their quality (Bass et al, 2010;Peled, 2013;Thurston, 2012). These observations lead us to our fourth hypothesis: H4: Datasets with more complete metadata will be downloaded more Finally, there is the extent to which datasets are updated.…”
Section: Explaining Downloads Of Open Government Datamentioning
confidence: 99%